PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH DALAM MEMBENTUK LOYALITAS NASABAH ( Studi Pada Nasabah Bank Jateng Kantor Cabang Koordinator Semarang - ANUGRAH UTAMA, 08.05.51.0094 ARDI; Maskur, Ali (Students Journal of Economic and Management, 2012)
This study aims to examine the effect of service quality dimensions which consist of tangible, reliability, responsiveness, assurance / confidence, empathy for the satisfaction, and loyalty to customers of Bank Jateng Office Coordinator Semarang Central Java. The population in this study were all customers of Bank Jateng Office Coordinator Semarang Central Java. This research used Purposive Accidental sampling by the number of respondents who captured 100 people. Research data collection is done by using a questionnaire. Data from the customer and then tested using factor analysis to test the validity of the statement items, test validity, reliability testing, regression analysis, determination coefficient and hypothesis test that includes a t test and F test. Based on data analysis and hypothesis test results obtained physical evidence that the quality of service tangible, reliability, responsiveness, assurance, and empathy has a positive and significant impact on customer satisfaction and satisfaction have a positive and significant impact on customer loyalty in which the dimension of responsiveness is the most dominant influence on customer satisfaction .Key words: Tangible, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction and Customer Loyalty